Establishment and Application of Ligation Reaction-Based Method for Quantifying MicroR-156b - He, Yuxuan; Long, Likun; Yan, Wei; Dong, Liming; Xia, Wei; Li, Congcong; Li, Feiwu (Frontiers in Plant Science, 2021)
Microribonucleic acids (miRNAs) play significant roles in the regulation of biological processes and in responses to biotic or abiotic environmental stresses. Therefore, it is necessary to quantitatively detect miRNAs to understand these complicated biological regulation mechanisms. This study established an ultrasensitive and highly specific method for the quantitative detection of miRNAs using simple operations on the ground of the ligation reaction of ribonucleotide-modified deoxyribonucleic acid (DNA) probes. This method avoids the complex design of conventional reverse transcription. In the developed assay, the target miRNA miR156b was able to directly hybridize the two ribonucleotide-modified DNA probes, and amplification with universal primers was achieved following the ligation reaction. As a result, the target miRNA could be sensitively measured even at a detection limit as low as 0.0001 amol, and differences of only a single base could be detected between miR156 family members. Moreover, the proposed quantitative method demonstrated satisfactory results for overexpression-based genetically modified (GM) soybean. Ligation-based quantitative polymerase chain reaction therefore has potential in investigating the biological functions of miRNAs, as well as in supervising activities regarding GM products or organisms.